A roadmap structure to integrate consumer behaviour for circular economy in apparel retail companies - Gomes, Giovana Monteiro (2022)
The textile industry influences traditions and lifestyles, having a crucial role in socio-cultural, political and economic dimensions. However, the textile industry is also responsible for extensive social and environmental impacts. The Circular Economy, as a disruptive economic model, presents solutions that prevent such impacts and intend to generate positive influences on society and the natural environment. Therefore, Circular Fashion, a new textile economy, encompasses stakeholders throughout the value chain, with a particular interest in the engagement of apparel consumers. This research aims to contribute to the promotion of the engagement of apparel consumers in circular consumption systems. To achieve that, a combination of methodological approaches was employed, including a systematic literature review on consumer behaviour and circular economy, a survey among Brazilian and Dutch apparel consumers, interviews with Brazilian apparel companies, and roadmap structure development. The results were presented in article format, gathering five papers. The first paper comprises the mapping of the Brazilian apparel value chain from a multi-level perspective, as well as its opportunities and challenges for the transition to a circular economy. The second, is the validation of the environmental psychology application in the circular economy field. The third, is the identification of consumers\' circular mindsets, behaviours, influencing factors and their role in circular consumption systems. The fourth, is the support that values, beliefs, and norms can predict consumer behaviour towards circular apparel, both in Brazil and in the Netherlands. At last, integrating the previous results, a roadmap structure was developed (fifth paper), gathering consumer behaviour, circular business model design, and communication and marketing strategies to guide apparel companies in engaging their consumers. This research, therefore, contributes to the field of consumer behaviour in the circular economy context and promotes consumer engagement in apparel circular consumption systems, assisting apparel brands to implement the circular economy\'s business models and principles.